2019
DOI: 10.1080/0284186x.2019.1659512
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the utilization of the decision to implement a palliative goal for the treatment of cancer patients during the last year of life at Helsinki University Hospital: a historic cohort study

Abstract: Background: To avoid aggressive treatments at the end-of-life and to provide palliative care (PC), physicians need to terminate futile anti-cancer treatments and define the palliative goal of the treatment in time. This single center study assesses the practices used to make the decision that leads to treatment with a palliative goal, i.e., the PC decision and its effect on anti-cancer treatments at the end of life. Material and methods: Patients with a cancer diagnosis treated in tertiary hospital during 1st … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…We have earlier demonstrated with this same cohort of patients [19] that a PC decision initiating the palliative goal for care was frequently made, but occurred late [11]: the median time from the PC decision to death was 46 days. Patients with no or a very late PC decision (<30 days) received more aggressive cancer treatments at the EOL and made fewer visits to the PC unit.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…We have earlier demonstrated with this same cohort of patients [19] that a PC decision initiating the palliative goal for care was frequently made, but occurred late [11]: the median time from the PC decision to death was 46 days. Patients with no or a very late PC decision (<30 days) received more aggressive cancer treatments at the EOL and made fewer visits to the PC unit.…”
Section: Discussionmentioning
confidence: 76%
“…In our earlier study [19], we reported that PC decisions done within the last month prior to death were associated with anti-cancer treatments continuing until close to death, and the access to a PC unit becoming more unlikely. Therefore, a well-timed decision to initiate a palliative period might also be related to more appropriate treatment and resource usage at the EOL.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations